First Evaluation of Associated Gut Microbiota in Wild Thick-Lipped Grey Mullets (Chelon labrosus, Risso 1827) - García-Márquez, Jorge; Isabel M., Cerezo; López-Figueroa, Félix; Abdala-Díaz, Roberto Teófilo; Arijo-Andrade, Salvador (IOAP-MPDI, 2022)
This study aimed to characterize the intestinal microbiota of wild thick-lipped grey mullets (Chelon labrosus) and explore its potential functionality on the host. Intestinal contents of anterior and posterior sections from wild fish were collected and DNA was extracted. Subsequently, the V3–V4 regions of 16S rRNA were sequenced using the Illumina technology and results were analyzed by bioinformatics pipeline. The functional profile of the microbial community was analyzed using PICRUSt software. Shannon and Simpson diversity indices were significantly higher in the posterior section of wild specimens. The overall taxonomic composition suggests a certain homogeneity in the anterior section of the intestine and heterogeneity in the posterior section. Due to this, no statistical differences were detected at any level among both intestinal sections. Predicted functions of intestinal microbiota showed the most abundant were those related to amino acid metabolism, carbohydrate metabolism, energy metabolism, membrane transport, and cell replication and repair. Furthermore, the analysis revealed microbial functional genes related to the elimination of environmental toxins.
Keywords: Saltamontes; Thick-lipped grey mullet; Mugilidae; Gut microorganisms; PICRUSt; Metabarcoding; Species diversification